Analysis of Performance of the Routing Protocols Ad Hoc using Random Waypoint Mobility Model Applied to an Urban Environment - Quezada Sarmiento, P. (2016)
Mobile ad-Hoc Network (MANET) is a group of mobile nodes interconnected and dynamic. A routing protocol is used to find the routes between the mobile nodes and facilitate the communication within the network. The aim of the protocols is to establish a correct and efficient route between a pair of mobile nodes, also it needs to be discovered and kept with a minimum consumption of bandwidth. This research work shows the performance assessment of six routing protocols: Destination Sequenced Distance-Vector (DSDV), Optimized Link State Routing (OLSR), Dynamic Source Routing Protocol (DSR), Ad Hoc On- Demand Distance Vector (AODV), Zone Routing Protocol (ZRP), Dynamic MANET On-Demand (DYMO). The evaluation was defined scenarios with 50, 90, 130, 170, 210 and 250 nodes and parameters such as: numbers of generated packages , broadcast packages, delay of node to node. The simulations and visualization from the results were executed in the network simulator NS2 version 2.34 and TraceGraph.